The rebel and the imam in early Islam : explorations in Muslim historiography - Haider, Najam Iftikhar, 1974- (Cambridge, United Kingdom : Cambridge University Press, 2019)
To what extent do contemporary approaches to the study of Islamic historiography reflect the presuppositions that informed the writing of early Muslim historians? A proper answer to this question requires a consideration of the classical and late antique periods. Numerous studies over the last fifty years have shown that Muslim political, social, and intellectual structures appropriated (and further elaborated) preexisting models. This claim is not universally applicable, but it seems to hold in areas ranging from coinage and court culture to legal codes and literature. A similar dynamic likely governed the relationship between late antique and early Muslim historical writing. At the very least, an approach that highlights such continuity promises a better understanding of the source material than does the current propensity to utilize categories drawn from a modern European context.
Modeling Islamic historical writing -- The rise and fall of Mukhtar b. Abi'Ubayd (d. 67/687) -- The life of Musa b. Ja'far al-Kazim (d. 183/799) -- The last years of Yahya b.'Abd Allah (d. 187/803) -- Reconsideration -- Appendix A. The narrative elements of Mukhtar's revolt.
Includes bibliographical references [pages 281-288] and index.
Keywords: Islamic Empire -- History -- 661-750 -- Historiography; Islamic Empire -- History -- 750-1258 -- Historiography